SAJAK AKAR NADIR: TRANSFORMASI KETERBATASAN MENUJU KEMANDIRIAN PEREMPUAN DALAM TARI KONTEMPORER (Avant-garde: Jurnal Ilmiah Pendidikan Seni Pertunjukan, 2026)
The creation of the contemporary dance work titled “Sajak Akar Nadir” is an artistic reflection on the struggles of women facing structural limitations, role demands, and social pressures until they successfully achieve self-sovereignty. This concept is inspired by the social reality in the film Pangku (2025) by Reza Rahardian, which was then transformed through the choreographer's personal emotional experience as an only daughter after losing her mother figure at a young age. Through the application of a dance creation method encompassing stages of exploration, improvisation, composition, and evaluation, this concept is manifested into a contemporary group dance in a dramatic-expressionist style involving 5 female dancers. Grounded in the idea that the body functions as a medium to voice unseen trauma and wounds, the visualization of this work utilizes spinning and balancing techniques rooted in the Batu Barajuik dance of West Sumatra. The work is enhanced through the symbolic integration of artistic elements such as dim lighting that creates a confined space of movement, minimal atmospheric stimulation from live techno music and vocals, as well as the use of props including threads wrapped around the head as a symbol of entanglement and stones interwoven into the hair as a symbol of perseverance in nurturing hope. The result of this dance demonstrates that the work positions women not as passive domestic objects, but as active, sovereign subjects who compose the "poem" of their own lives and attain the affirmation of independence precisely when they are at their lowest existential point (nadir).